Equity and excellence in education towards maximal learning opportunities for all students - Branden, Kris van den; Avermaet, Piet van; Houtte, Mieke van (Routledge research in education, 2011)
Throughout the world, equity and excellence in education is a major issue of concern. International comparative studies such as those carried out by OECD (PISA) have launched a worldwide debate on the effectiveness of educational systems (macro level), schools (meso level) and teachers (micro level) in terms of enhancing equity and excellence. Inspired by the OECD research and spurred by national policy-making, quantitative and qualitative research studies have recently been conducted in different parts of the globe aiming to provide deeper insight into the crucial variables that have an impact on equity, excellence or both. Among the variables that have been identified as crucial in this respect are the pupils' gender and their socio-economic and linguistic background, teachers' expectations, cognitions and pedagogical approach in the classroom, parental support, financial aspects, educational policies (e.g. priority policies, multilingual policies, early start policies), and variables related to the structure of the educational structure and system (e.g. compulsory school age, comprehensive systems, support structures, system variables enhancing spread of learners). This volume aims to compile a rich collection of research-based contributions, providing a state-of-the-art resource on what we know about this topic today. (Barnes & Noble)